REGRESSION MODELS OF THE DIMENSIONS OF THE DENTAL ARCH SHAPE IN GIRLS WITH A PHYSIOLOGICAL BITE AND A VERY WIDE FACIAL TYPE DEPENDING ON THE FEATURES OF TELERONTGENOMETRIC INDICATORS BY THE RICKETTS METHOD AND COMPUTED TOMOGRAPHIC DIMENSIONS OF THE TEETH - Brotskyi, N.O.; Dmitriev М.О.; Karliychuk, M.A.; Ocheretna, N.P.; Shevchuk, Yu.G. (World of Medicine and Biology, 2025)
In Ukrainian girls with physiological occlusion and a very wide face type, based on the features of teleradiometric indicators according to the Ricketts method and computed tomography dimensions of the teeth, all 18 possible reliable highly informative models (R2= from 0.626 to 0.913, p